Effect of Heat Treatment of Anodic Oxide Films on Aluminium on Their Photoluminescent Properties. (1976) - Tajima, S.; Shimizu, K.; Baba, N.; Sakai, H.
Abstract : Heating of anodic oxide films on aluminium produced irreversible changes in their photoluminescent properties. In the case of oxalic acid films, for instance, PL intensity increased exponentially with increasing heating temperature up to 600℃. Above this temperature, PL intensity decreased rapidly with increasing heating temperature and disappeared at 800℃. Similar tendencies were also found with other carboxylic and hydroxy-carboxylic acid films. On the other hand, inorganic acid films gave no photoluminescence even after heat treatment. It was found that our hypothesis that the luminescent centres of anodic oxide films on aluminium might be incorporated carboxylate ions as presented in a previous paper, proved to be appropriate to explain these observations.